Graphic Tools: Utilization of Glasses and Ceramics in Fine Arts - Shayma Haleem Naji (المجلة الدولية للعلوم الإنسانية والاجتماعية, 2021)
Fine art is known as "a visual art that is contemplate to have been originate in essence for artistic and creative purposes and evaluate for its beauty and full of meanings. This word "fine" does not express the aspect of the artistry in question, but the cleanliness of practice confers to traditional Western European canons. Graphic art spread expansive range of visual aesthetic interpretation, mainly 2-D, for example produced on a flat surface.  Exempt in the view of architecture, where efficient efficacy was accepted, this defines basically eliminate the "effective" applied or  embellishing arts, and the products were observed as crafts. In existent practice, these divergence and restraint have become originally meaningless, as the conception or objective of the artist is given authority, disregarding of the means through which this is expressed.